'Transcending Quotation': Cross-Cultural Musical Representation in Mauricio Kagel's Die Stücke der Windrose für Salonorchester - Heile, Björn (Saarbrücken VDM Verlag Dr. Müller, 2008)
In this doctoral dissertation, originally from 2001, Björn Heile analyses Mauricio Kagels groundbreaking cycle Die Stücke der Windrose für Salonorchester (1989-95) by relating it to Mikhail Bakhtins theory of dialogics and the postcolonial criticism of Edward Said. In a wide-ranging study, which includes in-depth investigations of primary sources such as the sketch materials and an interview with the composer, Heile develops a typology of cross-cultural musical representation which serves as the framework for a discussion of the different ways Kagel engages with his source materials. Throughout, the author moves between such issues as compositional technique, aesthetic questions, such as Kagels challenge to traditional notions of authorship, and the ideological implications of cross-cultural musical representation, which are interpreted in the light of recent discourses. By developing pioneering methodological approaches to cross-cultural composition, which has become a prominent feature of contemporary Western concert music, the book servesas a significant and innovative contribution to current discourses surrounding the musical representation of otherness.
Keywords: Kagel, Mauricio -- 1931-2008; Music history